Ethno-culture varieties of management culture and socio-normative prerequisites of its development - YASHNYK, Svitlana (Journal of Education, Technology and Computer Science, 2014)
The paper justifies socio-normative prerequisites for the formation of labourbehavior and management culture, highlights the cultural and ethnic variabilityof management culture; notes that ethnic mentality, social values, economicactivity, industrial relations and the system of according to ethnicity, sets specificdirection of the management culture.